Thermally Induced Displacements and Rotations of Pillars for Precise Geodetic Measurements - Robert Močnik; Dejan Zupan; Andrej Pal; Tomaž Ambrožič (Applied Sciences)
In this paper, we analyze the displacements of a geodetic reference pillar due to thermal loading, which typically occurs when the sunlit side of the pillar heats up more than the shaded side. This temperature differential induces bending of the pillar, resulting in the horizontal displacement of the screw used for forced centering of the instrument. Measuring displacement in the field is challenging, as it is difficult to thermally isolate the displacement sensor mount from the environment, whereas measuring rotations is much easier. Under controlled laboratory conditions, we measured the inclination of the plate with the forced-centering screw and simultaneously recorded the displacements near the top of a test pillar during a heating and cooling cycle totaling 10 h. During the heating phase, the heated side of the pillar recorded a temperature rise of 25.4 K, which led to a lateral displacement at the top of the pillar of approximately 1 mm. We found excellent agreement between the displacements calculated from the inclination and the directly measured displacements. The deviation between the calculated and measured displacements was less than 0.1 mm, which confirms the precision of the indirect method. Our results demonstrate that using an isolated inclinometer and converting the measured inclination values into displacements provides a representative characterization of the behavior of a pillar for precise geodetic measurements.